2016
DOI: 10.3357/amhp.4558.2016
|View full text |Cite
|
Sign up to set email alerts
|

Cognition Effects of Low-Grade Hypoxia

Abstract: The findings indicated a minimal influence of low-grade hypoxia on cognitive performance in contrast to some existing classic symptoms of hypoxia. Pilmanis AA, Balldin UI, Fischer JR. Cognition effects of low-grade hypoxia. Aerosp Med Hum Perform. 2016; 87(7):596-603.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 7 publications
4
15
0
Order By: Relevance
“…In addition, we found limited or no attentional impairment at the lower altitude of 3800 m for both hypoxic groups ( Fig 3 ). This finding potentially supports the results of Pilmanis et al [ 61 ], who reported a minimal influence of low-grade hypoxia on cognitive performance. The authors found small degradations in cognitive performance at simulated altitudes of 2438 m and 3658 m, but for only two of the cognitive tasks tested.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we found limited or no attentional impairment at the lower altitude of 3800 m for both hypoxic groups ( Fig 3 ). This finding potentially supports the results of Pilmanis et al [ 61 ], who reported a minimal influence of low-grade hypoxia on cognitive performance. The authors found small degradations in cognitive performance at simulated altitudes of 2438 m and 3658 m, but for only two of the cognitive tasks tested.…”
Section: Discussionsupporting
confidence: 92%
“…Peripheral oxygen saturations in our simulator group closely matched those recorded at equivalent altitudes in hypobaric hypoxia by Legg et al 17 and Pilmanis et al 30 ( Table IV). We plotted 95% confidence intervals for the metrics we measured in common 30 (this was to be expected: our subjects were wearing thick gloves and operating in a cold environment) and the baseline values for Logical Relations (ours were lower).…”
Section: Here]supporting
confidence: 88%
“…We chose the ANAM 4 battery (Cognitive Science Research Center, University of Oklahoma, OK), previously assessed as having good construct validity for its specified cognitive domains 34 and for its mood scale 14 , as well as minimal practice effects following second administration 4,11 . Given the variety of cognitive tests used in past studies, we deliberately chose our altitudes and test battery to be comparable with those used in two of the most rigorous previous studies: Legg et al 17 and Pilmanis et al 30 We selected the individual tests from the battery based on our experience of the demands of paragliding: logical reasoning (abstract reasoning), mannikin variation (spatial The subjects also undertook a Profile of Mood States (POMS) 24 test within the ANAM battery, where they were asked to describe how much a mood adjective applied on a categorical scale of 0 ('not at all') to 6 ('very much'), from the subcategories of anger, anxiety, depression/dysphoria, fatigue, happiness, restlessness and vigor.…”
Section: Equipment and Materialsmentioning
confidence: 99%
See 2 more Smart Citations